FEATURES OF DRILLING DETAILS MADE OF COMPOSITE POLYMER MATERIALS - Mamasodiqov Alisher Botirali o'g'li; Olimjonov Asrorbek Oybek o‘g‘li; Luqmonjonov Asadbek Bahodirjan o‘g‘li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The importance of polymer materials in the world economy is very great. In this article, the main conditions and features of drilling details made of these composite polymer materials are shown. It is also mentioned that during drilling, the walls of the hole are cracked, the edges of the hole are cracked, and because of this, the cuttings stick to the drill.